How to really ruin your financial life and portfolio - Stein, Benjamin 1944- (Wiley, 2012)
"Hilarious advice on what NOT to do with money, from financial funny man Ben Stein Everyone's searching for the secrets to financial success, but what about the best ways to lose money. fast?! In How To Really Ruin Your Financial Life and Portfolio, bestselling author, economist, financial commentator, and media personality Ben Stein explains exactly what to do. to go bust! The ultimate "how-NOT-to" guide, the book gives readers invaluable tips that should be avoided at all costs. Written in Stein's own inimitable style, this hilarious guide provides essential financial advice on what not to do when it comes to managing money. From reading and acting upon investing newsletters to trading on a margin, from investing in bonds to breathlessly following CNBC, and from buying stock in firms you do not understand to believing in your own genius at stock picking to keeping as little cash on hand as possible, Stein presents the rules that every would-be investor needs to know, so they can do the exact opposite and actually make money. Fully revised and updated, this new edition presents all-new missteps that can destroy any portfolio. Fully revised and updated edition of the tongue-in-cheek bestseller that shows investors what not to do with their money Written by acclaimed author economist, financial commentator, and media personality Ben Stein Loaded with indispensable pieces of bad advice that readers should avoid at all costs A laugh-out-loud approach to personal finance, How To Really Ruin Your Financial Life and Portfolio is an accessible guide to money from the funniest man in finance"--